Mitral and aortic regurgitation in Behçet's syndrome. Issue 9 (September 1985) - Peńa, J M; Garcia-Alegria, J; Garcia-Fernandez, F; Arnalich, F; Barbado, F J; Vazquez, J J
Abstract : A 35-year-old man with definite Behçet's disease developed acute mitral and aortic regurgitation. Valvular disease, we believed, was another manifestation of this disease. Cardiac involvement in Behçet's disease and the role of prednisone therapy are discussed.